The Multifunctionality of Source Citations and Indirect Speech in Arrian’s Anabasis of Alexander - Liotsakis, Vasileios (Histos, 2023)
Scholars tend to regard the citations of the Anabasis of Alexander as an expression of Arrian’s uncertainty or of the fact that he was drawing his information from sources other than Ptolemy and Aristobulus, while no efforts have been made to explore the functions of source citations and indirect speech in the work which move beyond the criteria of uncertainty and detachment. In this paper, I argue that Arrian took advantage of the traditional multifunctional potential of source citations and indirect speech in his Anabasis of Alexander, and in this way I reconsider the issue of how Arrian used his sources. My main argument is that in the Anabasis source citations, mostly the impersonal but occasionally the named ones too, are frequently aimed at emphasising the following four aspects: (a) a shift in the author’s interest towards biographical details about Alexander (his characterisation and a focus on his interpersonal relationships); (b) the author’s intention to digress from his linear historical narrative; (c) pivotal points of the enterprise; and (d) introducing or transitioning to a new event of the campaign.